Oral delivery of therapeutic proteins and peptides: a review on recent developments. (19th July 2013) - Gupta, Sonal; Jain, Arushi; Chakraborty, Mainak; Sahni, Jasjeet K; Ali, Javed; Dang, Shweta
Abstract: Advent of recombinant technology in protein synthesis has given birth to a new range of biopharmaceuticals. These therapeutic peptides and proteins are now emerging as an imperative part of various treatment protocols especially in the cancer therapeutics. Despite extensive research efforts, oral delivery of therapeutic peptide or protein is still a challenge for pharmaceutical industries and researchers. Number of factors including high proteolytic activity and low pH conditions of gastrointestinal tract act as major barriers in the successful delivery of intact protein/peptide to the targeted site. Low permeability of protein/peptide across the intestinal barrier is also a factor adding to the low bioavailability. Therefore, because of the short circulatory half-life exhibited by peptides in vivo, they need to be administered frequently resulting in increased cost of treatment and low patient compliance. Nano-carrier-based delivery presents an appropriate choice of drug carriers owing to their property to protect proteins from degradation by the low pH conditions in stomach or by the proteolytic enzymes in the gastrointestinal tract. This review focuses on recent aspects and patents on oral delivery of therapeutic proteins and peptides with special emphasis on nano-carrier-based approach.